Development of Islamic Cultural History (SKI) Teaching Materials Based on Self-Directed Learning for University Students - Maryam; Rizal, Syamsul; Puspitasari, Arum; Yuhaswita; Bety (LETIGES, 2024)
The use of teaching materials for the History of Islamic Culture Madrasah Ibtidaiyah (SKI MI) Course in the Madrasah Ibtidaiyah Teacher Education study program has yet to include self-directed learning to improve learning outcomes. Therefore, this study aims to develop teaching materials for the History of Islamic Culture Madrasah Ibtidaiyah (SKI MI) Course based on self-directed learning for students of the Madrasah Ibtidaiyah Teacher Education Study Program (PGMI). The research method is Research and Development, with a qualitative approach to collect data from interviews and observations and a quantitative approach to obtain data from surveys and experimental tests. The development model used is the development of Borg and Gall. Research results include: First, teaching materials for the History of Islamic Culture Madrasah Ibtidaiyah (SKI MI) Course based on self-directed learning to improve learning outcomes. Second, teaching materials are developed in 7 stages by the development of Borg and Gall. Third, the teaching materials are assessed from the material with an ideality reaching 88%, presentation with an ideality reaching 83%, language with an ideality reaching 86%, and graphics with an ideality reaching 90%. From several presentations, it is valid and practical with an ideality of 85% and effective with an Equal Variance Assumed of 0.007, effectively improving student learning outcomes. This study is limited to developing teaching materials without exploring other aspects of the learning process, such as teaching methods, teacher involvement, or the context of the learning environment that may affect student learning outcomes. The originality of this article is the development of SKI MI teaching materials based on independent learning using the Borg and Gall model.